Influence of the mct1-t1470a polymorphism (rs1049434) on repeated sprint ability and blood lactate accumulation in elite football players: a pilot study - Massidda, M.; Flore, L.; Kikuchi, N.; Scorcu, M.; Piras, F.; Cugia, P.; Cieszczyk, P.; Tocco, F.; Calò, C. M. (European Journal of Applied Physiology, 2021)
Purpose The aim of this study is to investigate the influence of the MCT1 T1470A polymorphism (rs1049434) on repeated sprint ability (RSA) and lactate accumulation after RSA testing.